O Princípio do contexto de Gottlob Frege: O labirinto de sua exegese - Souza, Izabel Cristina Izidoro de (2014)
This research approaches the logicist project of the German philosopher, Frege, and what came to be named by the secondary literature as the “Context Principle”. Frege's logicist project is the thesis that Mathematics, specially Arithmetics, can be reduced to Logics, that is, the concepts of Arithmetics can be reduced to logical concepts and to logical theorem and axioms. The Context Principle is one of the three principles that Frege afirms to be basic for the development and execution of a project. Some questions arise to the reader that faces for the first time this principle: What a Mathematical thesis – the one that Arithmetics can be reduced to Logics has to do with a linguistic imposition – the one that we should never ask for the meaning of an isolated word, outside a sentence? The secondary literature seems to not come to any agreement about the questions around the context principle. Those questions conduct the methodological aspect of this research. The use of the Greek mith of Theseus and Daedalus labyrinth as a metaphor allows to understand the set of secondary literature interpretations regarding the context principle as an exegetical labyrinth that defyies the reader to come inside it and try to exit. At the end of the research considerations will be give about the fortune of the context principle in Frege's logicist project.